2016
DOI: 10.1089/dia.2015.0425
|View full text |Cite
|
Sign up to set email alerts
|

CoYoT1 Clinic: Innovative Telemedicine Care Model for Young Adults with Type 1 Diabetes

Abstract: In this cross-sectional pilot study, the CoYoT1 Clinic, incorporating Web-based videoconferencing and peer interactions, was feasible and acceptable for young adults with T1D. This model may potentially increase engagement with diabetes care in the young adult population. However, further research is needed to fully evaluate the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
100
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(104 citation statements)
references
References 20 publications
4
100
0
Order By: Relevance
“…12 In another study on 18-55-year-old patients with T1D, there was a tendency toward less impact of diabetes on quality of life in the group receiving telemedicine visits (P = 0.061). 13 Additional benefits of telemedicine were increased attendance at visits, 15,16 less time spent traveling to and attending visits, 11,13,17,18 and lower cost. 11,13 In addition, the use of telemedicine versus in-person visits did not affect the therapeutic relationship between providers and adolescent patients 19 and may actually empower patients to better manage their diabetes.…”
Section: Virtual Education and Medical Visitsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In another study on 18-55-year-old patients with T1D, there was a tendency toward less impact of diabetes on quality of life in the group receiving telemedicine visits (P = 0.061). 13 Additional benefits of telemedicine were increased attendance at visits, 15,16 less time spent traveling to and attending visits, 11,13,17,18 and lower cost. 11,13 In addition, the use of telemedicine versus in-person visits did not affect the therapeutic relationship between providers and adolescent patients 19 and may actually empower patients to better manage their diabetes.…”
Section: Virtual Education and Medical Visitsmentioning
confidence: 99%
“…11,13 In addition, the use of telemedicine versus in-person visits did not affect the therapeutic relationship between providers and adolescent patients 19 and may actually empower patients to better manage their diabetes. 13,17,18 Virtual environments, which are Internet-based real-time computer-generated three-dimensional representations of a contrived or natural environment in which patients and clinicians self-represent as avatars, 20 are also being studied as a means of providing diabetes self-management (DSM) education to a greater number of individuals. Preliminary results suggest that virtual environments may be another viable means of overcoming both a shortage of diabetes clinicians and barriers to accessing in-office care.…”
Section: Virtual Education and Medical Visitsmentioning
confidence: 99%
“…In our previous prospective non-randomized trial, which enrolled T1D YA patients from a fairly homogeneous background (age 19.8 ± 1.6 years, 83% White, 86% Non-Hispanic, and 86% privately insured), enrollees who participated in CoYoT1 Clinic had improved clinic attendance compared to control group patients (71% of CoYoT1 patients attended four clinic visits over the study year, meeting ADA recommendations, versus 0% of control group patients), and trended towards completing HbA1c tests more frequently than control patients [24,25]. Patients in the CoYoT1 intervention also reported decreased diabetes distress, increased confidence in their abilities to manage their diabetes, and improved ability to communicate with others about their diabetes, compared to the control group.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CoYoT1 patients reported a lower level of psychosocial burden associated with diabetes care over the course of the study year, whereas patients receiving standard care reported higher levels. Cumulatively, CoYoT1 patients experienced both increased clinical engagement and psychosocial improvements, while also maintaining glycemic control [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation